History of falls and fear of falling are predictive of future falls: Outcome of a fall rate model applied to the Swiss CHEF Trial cohort - Wapp, Christina; Mittaz Hager, Anne-Gabrielle; Hilfiker, Roger; Zysset, Philippe (Frontiers in Aging, 2022)
Background: A third of adults aged 65 years and older fall every year, and falls are a common cause for unintentional injuries. The correct identification of people at risk for falling is an important step for preventive strategies. Objective: To investigate the association of fall risk factors to the number of reported falls in terms of incidence rate ratios, and the development of a fall rate prediction model. Methods: In the randomized controlled trial SwissCHEF, different fall risk variables were assessed at baseline examination including age, sex, body mass index, fear of falling, number of falls 12 months prior to examination, physical performance tests, comorbidities, and quality of life in community-dwelling older adults. In the subsequent year, the intervention of two home-based exercise programs was conducted. Falls were reported prospectively with monthly calendars. Incidence rate ratios were derived with negative binomial regression models. Variable selection for the prediction model was conducted with backward elimination and least absolute shrinkage and selection operator. The model with the smallest prediction error was identified. Results: Associations to the reported falls were found for prior falls, fear of falling, balance and gait deficits and quality of life. The final model was derived with backward elimination and included the prior fall number and a measure for fear of falling. Outcome: Prior fall number together with fear of falling are predictive for a personalized fall rate estimate in community-dwelling older adults. Recurrent fallers having experienced four or more falls are especially at risk to fall again. Trial Registration Number: NTC02926105, https://clinicaltrials.gov/ct2/show/NCT02926105